The Organizational Culture As A Moderate For Motivation And Transformational Leadership On Employe Performance: A Literature Review - Majid, Abdul (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to explore the relationship between organizational culture, employee motivation, transformational leadership, and employee performance. In this literature study, the authors reviewed various journal articles that discussed the topic. The results of the literature analysis show that organizational culture has an important role as a mediator in influencing employee motivation and transformational leadership on their performance. A strong and positive organizational culture can increase employee intrinsic and extrinsic motivation and create a work environment that supports innovation, team collaboration, and self-development. In addition, transformational leadership was also found to have a significant impact on employee motivation and directly contribute to improving individual and group performance. This leadership style is able to inspire subordinates with a clear vision, provide emotional support, empower team members to achieve common goals. However, although there is much evidence about the positive relationship between organizational culture, employee motivation, and transformational leadership and employee performance, it should be remembered that each organizational context has unique and complex characteristics. Therefore, further research is needed to deeply understand this relationship in various industrial sectors and different organizational cultures. In conclusion, literature studies indicate that organizational culture, employee motivation, and transformational leadership are interrelated and have a significant influence on employee performance. In an effort to increase productivity and organizational success, it is important for managers to create a positive work culture, encourage both intrinsic and extrinsic motivation of employees and carry out transformational leadership effectively.